The Influence of the Proportion of Bones and Meat Catfish (Clarias batrachus) and Frying Time on the Quality of Catfish Floss - Qotima, Khusnul; Winarti, Sri (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Catfish is a freshwater fish that is often found but has not been used optimally. One alternative use of catfish is processed into catfish floss. This research aims to determine the effect and best treatment of the proportion of bones and meat of catfish with frying time. This research used a completely randomized design (CRD) factorial with 2 factors and 2 replications. Factor I is the proportion of bone: meat of catfish (30:70, 50:50, 70:30). Factor II is the frying time (60 minutes, 90 minutes, 120 minutes). Observation data were analyzed using ANOVA with a level of 5%. If there were significant differences between treatments, the DMRT test was continued. The best treatment in this study was a long frying treatment of 60 minutes with the proportion of bone: catfish meat (30:70) producing shredded catfish with calcium levels (6.78%), water content (8.81%), ash content (7.04%), fat content (27.02%), TBA number (0.18mg.MDA/kg), color scoring test 1.28 (yellow) and aroma scoring test 4.48 (slightly burnt).